Triangular UFOs: An Estimate of the Situation by Dave Marler - Alexander, John B. (Journal of Scientific Exploration, 2016)
For truth in advertising, the reader should know that I wrote the Foreword to this book a few years ago. It, therefore, should be obvious that I was positively disposed to the content. There is, however, a good reason for my support of his work. Dave Marler is a superb researcher with a very methodic and conscientious approach to the UFO topic. Most importantly, he is careful not to say more than he can back up with hard data. His research efforts are supported by one of the most meticulously kept UFO archives anywhere, which he maintains at his home near Albuquerque. It is replete with rare documents and rightfully would make most other UFO researchers envious. In truth, the pristine condition of his archives is indicative of the care he puts into all of his activities. For this book Marler’s approach entails comprehensive research into an important subset of the UFO phenomena; something that no one else has attempted previously. While several people have written short papers about triangular UFOs, his efforts are in-depth and compelling. I was particularly impressed as it circumvented one of my main concerns; i.e. “What constitutes a UFO?” Unfortunately, it is a term used broadly and without clear definition. Reports of UFOs range from little balls of light, often high in the sky, to large physical objects, possibly more than a mile across. Besides objects small and far away there are other observations by credible witnesses at very close proximity to the craft. There should be real concern about the enormous variability in observations when considering this global issue. There are just too many varieties of craft to accommodate any single simple solution. Positing little grey guys from Zeta Reticula, who have come to collect sperm, or more perversely, conduct anal probes, just won’t do it. To his credit, Marler avoids pronouncing the craft as extraterrestrial. For him the provenance is just unknown.